The effect of semestrial sportifs exercises on enhancing mental and motor imagery patterns ” Case study on students from the faculty of sports educations” - كفا عزيز (Latakia University Journal -Medical Sciences Series, 2023)
The aim of the research is to find out the impact of semestiral sports exercise on boosting the patterns of mental and motor Imagery, without direct and voluntary training of mental perception, as well as to see whether there is a difference in the level and patterns of mental and motor perception as semestiral sports training accumulates for students of the Faculty of Sports Education? In the study, a questionnaire was used to measure the perception of sport, designed by Martens (1982) and Arabized (2007) on a sample of 176 volunteers (male and female) from the Faculty of Physical Education, Tishreen University, in their first and second years. The results of the study showed that the first and second year students of the Faculty of Physical Education had a medium and good motor mental perception level (respectively), which an acceptable mental perception degree is after the accumulation of quarterly sports training, which proves the validity of our first hypothesis. It was also found that the students of the Faculty of Physical Education for the second year have a good motor mental perception level, which is a higher level than the mental perception level of the first year, which proves the validity of our second hypothesis.